(untitled) (LACCEI, 2024)
Abstract: Road infrastructure contributes to urban zones’ economy, labor, and social dynamism. In this sense, the measurement of the driver’s behavior and perception becomes crucial. It is due to these facts that this study delves further into it, having the Central District’s city as the main scenario, the capital of Honduras. For which a quantitative correlational design with a sample of 385 drivers was considered for such a study, to whom an instrument in digital format was applied through the Qualtrics XM APP. Reaching a Cronbach’s Alpha of 0.735, then a factor model was developed through an AFE in which the final results of the eigenvalues were greater than 1 showing the existence of four factors, whose Bartlett test sphericity was significant (χ2= 1539.14, gl= 105, Sig.= .001) and the adequacy indicator of the sample size (KMO =.753) was appropriate. Likewise, the AFC confirms the exploratory factorial structure, emitting correlational values between the behavior dimension before the signaling and the behavior before the road infrastructure, and a correlation between the perception of residential road infrastructure and the behavior regarding the state of the infrastructure. Therefore, it is concluded that the scale is supported by an adequate model based on four factors distributed in 15 items. In turn, at a descriptive level was noted that three are the busiest communication roads in Central District.